ANALISIS REKSADANA SYARIAH DALAM SISTEM PASAR MODAL SYARIAH DI INDONESIA - Fatimah; Noor Helmalia Agus; Muhammad Rafi; Muhammad Muallifurrahmi Arramidly (PT. Saha Kreasi Indonesia, 2026)
Islamic mutual funds are one of the investment instruments that have experienced significant growth within Indonesia's Islamic capital market system. The existence of Islamic mutual funds provides an investment alternative for individuals seeking financial returns while adhering to Islamic principles. This study aims to analyze the role, mechanism, development, and contribution of Islamic mutual funds in supporting the growth of the Islamic capital market in Indonesia. The research employs a qualitative method with a literature review approach by collecting and analyzing data from scientific journals, books, regulations issued by the Financial Services Authority (OJK), fatwas of the National Sharia Council-Indonesian Ulema Council (DSN-MUI), and various publications related to the Islamic capital market. The findings indicate that Islamic mutual funds differ from conventional mutual funds because all investment management activities and asset allocations must comply with Sharia principles and avoid elements of riba (interest), gharar (uncertainty), and maysir (gambling). Furthermore, the development of Islamic mutual funds in Indonesia has shown a positive trend due to increasing public awareness of Sharia-compliant investments and the support of regulatory frameworks established by OJK. Islamic mutual funds also contribute to expanding Islamic financial inclusion and strengthening the national Islamic capital market ecosystem. Therefore, Islamic mutual funds play a strategic role in promoting the growth and sustainability of Indonesia's Islamic financial industry.